The day they parachuted cats on Borneo; a drama of ecology - Pomerantz, Charlotte; Aruego, Jose ([Reading, Mass.] : Young Scott Books, 1971)
Describes in rhyme the destruction of Borneo's ecological balance when DDT, used to kill the malaria-spreading mosquitoes, also killed the cats, causing a plague of rats, and literally brought the roofs down on the farmers' heads.
Mode of access: Internet.
Keywords: Pesticides -- Environmental aspects -- Juvenile literature; DDT (Insecticide) -- Juvenile literature